Telecommunications liberalization on two sides of the Atlantic - Cave, Martin; Crandall, Robert W. (AEI-Brookings Joint Center for Regulatory Studies, 2001)
The 1990s witnessed a major revolution in telecommunications policy in North America and Europe. The electronics revolution swept the world, and most countries began to realize that they could not compete in many markets without a vibrant, competitive telecommunications sector. As a result, the European Union, Canada, and the United States launched major new liberalization policies aimed at opening all telecommunications markets to competition. This report presents two views of the progress towards competition-one for North America and one for Europe. The authors provide an overview of the market structure on both continents prior to the 1990s, discuss significant regulatory changes during that decade, and analyze changes in rate structures and competition that have occurred since liberalization. They conclude with a look at the present and future impact of the Internet and other new technologies on the telecommunications industry.